Studies carried out in Portugal in the area of peripheral venous catheterization: scoping review protocol - Santos-Costa, Paulo Jorge dos (2020)
Background: Despite its ubiquitous nature, the practice of peripheral venous catheterization is not homogeneous among international clinical contexts. In Portugal, the information regarding the practice of peripheral venous catheterization is scattered in the literature, hindering efforts of a comprehensive analysis of its nature and implications. Objective: To map the studies developed in Portugal in the field of peripheral venous catheterization. Review method: Scoping review methodology proposed by the Joanna Briggs Institute. An adequate protocol was established for each base/repository to identify studies that meet the criteria outlined. The analysis of data relevance, extraction, and synthesis will be performed by independent reviewers. Presentation and interpretation of results: The mapping of the studies carried out in Portugal in this area will contribute to the identification of the main structure, process, and outcome indicators described in national studies. Conclusion: It is expected that this review will support the development of future interventions and systematic reviews that enhance the efficacy/safety of the care provided to patients with a peripheral catheter.